Shades of Gray in the War in Eastern Ukraine: ‘Neither War nor Peace’ Existence Zones, ‘Neither Truth nor Lie’ Silence Zones - Bulyk Maxim; Gridina Irina (Baltic Journal of European studies, 2019)
The concepts of ‘gray zone conflict’, as one of the new phenomena in the theory of international relations, are given considerable attention in modern strategic researches of analysts, in particular American ones (Hel Brands, Adam Elkus, etc.). The definition of ‘gray zone conflict’ by American political scientists coincides with the definitions of domestic scholars in outlining the hybrid war in general, and Russian Federation’s war against Ukraine in particular. At the same time, qualifying the aggression of the Russian Federation against Ukraine and the war in Eastern Ukraine as the sole concept of ‘gray zone’ shall be considered not to be entirely correct, since the scales tend to favor the definition of civil war, which is so advantageous to Vladimir Putin. On the other hand, the war in Eastern Ukraine has many shades of gray, which gives grounds to the use of the concept of ‘gray zone conflict’ on specific examples of the existence of real and imaginary gray zones (realities of existence and zones of silence) and to investigate their quantitative and qualitative characteristics, to determine the degree of the viral use of the gray zone of conflict by the state (as an object of aggression), which complicates its establishment. The possibilities/unacceptability of solving gray zone conflicts by “gray” methods are being outlined as well.